Paul - Bornkamm, Gunther; Stalker, David M.G. (San Franscisco Harper and Row, 1971)
Includes bibliographical references and indexes.
Originally published as : Paulus, Stuttgart : W. Kohlhammer GmbH, 1969.
Keywords: Paul, the Apostle, Saint -- biography